2017
DOI: 10.4103/2229-516x.198526
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of dentinal hypersensitivity using low-level laser therapy and 5% potassium nitrate: A randomized, controlled, three arm parallel clinical study

Abstract: Aim:The present randomized study was aimed to compare the efficacy 5% potassium nitrate (KNO3) toothpaste, low-level laser therapy (LLLT), and LLLT with 5% KNO3 toothpaste in the treatment of dentinal hypersensitivity (DH).Materials and Methods:Total of 45 patients complaining of DH with visual analog scale (VAS) score being ≥2 were recruited and were divided into three groups. Group A was treated with 5% KNO3 toothpaste, Group B using LLLT along with the application of 5% KNO3 toothpaste, and Group C using LL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In previous studies, authors demonstrated the possibility to occlude dentinal tubules by means of different wavelengths. Ruchi Pandey et al [37], concluded that low-level laser therapy with diode laser 810 nm at 0.5 W was able to reduce dentinal hypersensitivity [37]. Anely Oliveira Lopes et al, used different protocols combing the laser and desensitizing agents, and revealed that all treatments reduce DH [38].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, authors demonstrated the possibility to occlude dentinal tubules by means of different wavelengths. Ruchi Pandey et al [37], concluded that low-level laser therapy with diode laser 810 nm at 0.5 W was able to reduce dentinal hypersensitivity [37]. Anely Oliveira Lopes et al, used different protocols combing the laser and desensitizing agents, and revealed that all treatments reduce DH [38].…”
Section: Discussionmentioning
confidence: 99%
“…The dentine sensitivity (DS) is a common dilemma in adults' population with a prevalence ranging from 8 to 57% [ 1 ] and is ascribed in routine dental practice perceived generally from the second to sixth decade of life [ 2 ]. It has a multifactorial etiology and is described clinically as an acute pain caused by excitation of A delta nerve fibers connected to exposed dentine and its tubules due to chemical, thermal, osmotic, evaporative, or tactile stimulation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, laser irradiation was proven efficient for DH treatment [21][22][23][24]. In our study, diode laser was chosen as an LLLT appliance, and it was successfully implemented.…”
Section: Discussionmentioning
confidence: 99%
“…It could be explained that all these studies were performed using different diode lasers, with a wide range of wavelengths of 635-830 nm and dosages of 2-10 J/cm 2 . The usage of all these parameters is acceptable and does not affect the morphology of enamel or dentine surface [12][13][14][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%